P2.37 Presence of genital chlamydia trachomatis serotype l2 infection in south african women. (8th July 2017) - Peters, Remco; Redelinghuys, Mathys; Mcintyre, James; Doyle, Ronan; Verjans, Georges; Breuer, Judith; Kock, Marleen
Abstract : Introduction: Chlamydia trachomatis serotype-L, lymphogranuloma venereum (LGV), is a well-recognised infection among men who have sex with men in developed nations. In Africa, LGV is an uncommon but recognised cause of genital ulcer disease in men and women. The presence of genital infection in African women is unknown. Methods: In this pilot study we evaluated the presence of C. trachomatis serotype-L in 55 vaginal specimens that tested positive for C. trachomatis . These specimens were obtained in several studies over the period 2012–2016 that recruited women visiting a mobile health clinic in rural Mopani District (n=25) and in various settings in Pretoria: a tertiary obstetrics and gynaecology clinic (n=14), an antiretroviral treatment (ART) clinic (n=10) and a sexually transmitted infections (STI) clinic (n=6). Presence of serovar type-L of C. trachomatis was assessed using a targeted PCR assay and confirmed by whole-genome sequencing (WGS) of DNA from the clinical specimen. Results: We identified serotype-L C. trachomatis infection by targeted PCR in 8 cases. All of these women had presented with vaginal discharge at either the ART (n=5) or STI (n=3) clinic. Two women had co-infection with Neisseria gonorrhoeae, two with Mycoplasma genitalium and two with Trichomonas vaginalis . WGS of 5 specimens confirmed the presence of the L2 serovar. Also, one mixed infection of serovars L2 and E (minority) was observed. Conclusion: This pilot study demonstrates the presence of symptomatic cervical infection by C. trachomatis of serotype-L2 in African women. This confirms one report of (chronic) genital infection in African women from more than two decades ago. The significance of this observation is to be determined with regards to virulence, morbidity, distribution across the population and clinical management in the current context of the syndromic approach